PENGARUH PEMBELAJARAN JARAK JAUH DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PRODUK KUE INDONESIA - Munawaroh, Fauziyah; Soetisna, Ari Fadiati Wira; Alsuhendra; Wastira, Jarudin (Jurnal Pendidikan Teknik dan Vokasional, 2021)
This research aims to know the influence of distance instructional strategies and learning motivation on the results of learning to make Indonesian cake products. Using research methods with quantitative approaches. Research design with factorial 2X2. Variable distance learning strategies using the Google Classroom (A1) and Zoom Meeting Cloud (A2) apps. The variables of learning motivation are high learning motivation (B1) and low learning motivation (B2). The instrument used to measure students' learning motivation is a questionnaire with a Likert scale. It involved 66 respondents who were divided into two groups as experiments and controls. The results of the first hypothesis test that Sig. 0.086 >0.05 can mean no difference in learning outcomes between students treated through Google Classroom and students treated through Zoom Meeting Cloud. The second hypothesis is that Sig. 0.000<0.05 can be interpreted as a significant difference in learning outcomes between students who have high learning motivation and low learning motivation. The third hypothesis is that Sig. 0.001<0.05 can mean there is an interaction between learning strategies and learning motivation. He concluded that the instructional process does not have differences in learning outcomes while knowing there are differences in learning outcomes. This research's implications need to be reviewed in applying instructional strategies in the experimental learning process because vocational school students are required to have competencies. This research is new to the understanding of theory. Keywords: Instructional Strategies, Learning Motivation, learning platform, Indonesian Cake Products